SEMINAR PUBLIC SPEAKING DAN EVENT ORGANIZER PADA PERANGKAT DESA SUNGAI SERABEK KECAMATAN TELUK KERAMAT KABUPATEN SAMBAS - M. Sabiqul Huda; Muhammad Asyura; Syaifudin Syaifudin (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
This Community Service Program (PKM) is a community-based program that aims to improve public speaking skills and event management skills on the device of Sungai Serabek Village, Teluk Keramat District. This PKM reviews about public speaking theory by Arih Budi Utomo with its motto ideas namely IDEAS (Inner power, Delivery, Effect, Authentic, and Self Assessment). In addition, participants also studied the differences between discussions, seminars, symposiums, and workshops which are some of the terms of organizing formal events handled by event organizers. The results of this PKM showed that participants were very enthusiastic to follow what can be seen from the list of presents that meet the targets, the running of question and answer sessions, and interactions during the seminar. The majority of participants are village devices that often become MCs or community leaders in various types of formal and non-formal events feel helped by this seminar and become an exchange of ideas and experiences.